2011
DOI: 10.1111/j.1865-1682.2010.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Detection of PCV2 and Anti-PCV2 Antibody in Oral Fluids Following Experimental Inoculation

Abstract: The onset, level and duration of PCV2 and anti-PCV2 antibody in oral fluid were evaluated using samples collected from experimentally inoculated pigs for 98 days post-inoculation (DPI). Pigs (n = 24) were obtained at 3 weeks of age and randomly allocated to 4 treatment pens of 6 pigs each: (i) negative control group; (ii) inoculated with PCV2a (strain ISU 40895) on DPI 0; (iii) inoculated with PCV2a (strain ISU-40895) on DPI 0 and re-challenged at DPIs 35 and 70; (iv) inoculated with PCV2a (ISU-40895), PCV2b (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…4,17,23,24 The oral fluid collection from individual young piglets showed, however, not to be straightforward and was largely dependent on individual animal behavior. Although the animals were trained to chew on the ropes in 1 week, and oral fluid sampling was conducted before physically manipulating the animals, in the current study, only 2 pigs chewed at every time point, while 2 other pigs would not chew on the ropes throughout the entire experiment.…”
Section: Discussionmentioning
confidence: 99%
“…4,17,23,24 The oral fluid collection from individual young piglets showed, however, not to be straightforward and was largely dependent on individual animal behavior. Although the animals were trained to chew on the ropes in 1 week, and oral fluid sampling was conducted before physically manipulating the animals, in the current study, only 2 pigs chewed at every time point, while 2 other pigs would not chew on the ropes throughout the entire experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, collecting oral fluid specimens requires less labor, is stress free for both animals and human beings, and is a sensitive method for detecting infections in populations. 5,[9][10][11][12] For these reasons, oral fluid sampling has been rapidly adopted by producers and veterinarians and has become routine on many farms. At the Iowa State University Veterinary Diagnostic Laboratory (Ames, IA), the specimen type "swine oral fluid" was entered into the laboratory information management system in February 2010.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][9][10][11][12] While PCR-based assays are useful for detecting the immediate circulation of pathogens, antibody-based assays are informative regarding herd immunity and the history of an infection in the population. Because both assays reflect different phases of infection, the best test can be selected to serve the need.…”
mentioning
confidence: 99%
“…Available from: http://nationalhogfarmer.com/health-diseases/disease-prevention/oral-fluid-collection-enhances-testing-0915). 2,9,[14][15][16][17]19 In 2013, studies reported the experimental detection of FMDV genome or ASF virus (ASFV) antibody in swine OF samples. 13,24 Specifically, OF is defined as the fluid in the oral cavity collected by use of an absorptive device.…”
Section: Research-article2015mentioning
confidence: 99%